2019
DOI: 10.1159/000495511
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Distress Syndrome following Cardiac Surgery: Comparison of the American-European Consensus Conference Definition versus the Berlin Definition

Abstract: Background: Lung injury with development of the acute respiratory distress syndrome (ARDS) is a serious complication which can occur after major surgery, including cardiac surgery. Objective: The aim of our study was to compare the prevalence, risk factors, and mortality of ARDS following cardiac surgery according to the American-European Consensus Conference (AECC) definition and the new Berlin definition of ARDS. Methods: We performed a retrospective, observational study that included prospectively collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…In this case organs, failure can also be seen. Reduce urination, high level of bilirubin, high lactate level, acidosis and thrombocytopenia were also observed [4,20,25].…”
Section: Symptoms Of Covid-19mentioning
confidence: 89%
See 2 more Smart Citations
“…In this case organs, failure can also be seen. Reduce urination, high level of bilirubin, high lactate level, acidosis and thrombocytopenia were also observed [4,20,25].…”
Section: Symptoms Of Covid-19mentioning
confidence: 89%
“…The illness is characterized by some following stages and their symptoms: For mild stage, illness is characterized by no sign of pneumonia and other serious illnesses like diarrhea and dyspnea. But the other symptoms include infection of an upper respiratory tract, fever, dry cough, sore throat, nasal discharge, sneezing, pain in muscles and headache sometimes [4,25]. In China, there were 81% of such cases were calculated.…”
Section: Symptoms Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological data suggested that the lungs of patients who undergone for lung lobectomies due to adenocarcinoma got infection at the time of surgery. Vascular congestion and inflammatory fibrinoid and hyperplasia of pneumocytes were also seen in other patients (69). According to the International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3), gives a life-threatening organ dysfunctioning (74).…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory insufficiency severity and the diagnostic criteria of septic shock and sepsis can be used as a reference 55 .…”
Section: International Journal Of Pharmaceutical Sciences Review and mentioning
confidence: 99%